Association of Acne with Face Mask in Healthcare Workers Amidst the COVID-19 Outbreak in Karachi, Pakistan - Yaqoob S; Saleem A; Ahmad Jarullah F; Asif A; Essar MY; Emad S (Dove Medical Press, 2021)
Sadia Yaqoob,1 Amna Saleem,1 Furqan Ahmad Jarullah,1 Areeba Asif,1 Mohammad Yasir Essar,2 Shaista Emad3 1Department of Medicine, Jinnah Medical and Dental College, Karachi, Pakistan; 2Department of Dentistry, Kabul University of Medical Sciences, Kabul, Afghanistan; 3Department of Biochemistry, Sohail University, Karachi, PakistanCorrespondence: Mohammad Yasir EssarDepartment of Dentistry, Kabul University of Medical Sciences, Kabul, 1001, AfghanistanEmail yasir.essar@gmail.comBackground: In the wake of coronavirus (COVID-19) global alert, people have begun to practice safety measures in order to reduce the exposure to life-threatening disease. The largest at risk population is undoubtedly the frontline healthcare workers (HCWs) who are using personal protective equipment (PPE), essentially face masks, to battle against this deadly virus. This study was conducted with the prime intention to reveal an association between face mask and acne and measure the prevalence of acne amongst HCWs amidst COVID-19 outbreak in Karachi. Furthermore, this study aimed to identify the type of mask generating acne, locate the common sites, assess the severity and establish an association of mask use with the skin type.Methods: This cross-sectional study was carried out at Medicare Cardiac and General Hospital, Jinnah Medical College Hospital, Jinnah Postgraduate Medical Centre and Jamal Noor Hospital located in Karachi, Pakistan. A total of 348 HCWs were interviewed, of which only 193 met the inclusion criteria. All information was recorded on a predesigned proforma and analyzed using SPSS 25.0.Results: Among 193 participants, acne was prevalent in 103 (53.4%) participants with maximum cases reported in female HCWs, and in doctors (p< 0.05). Out of 73 HCWs using N-95 masks, 46 (44.7%) developed acne, with a p-value of 0.036. Skin type and past history of acne also yielded statistically significant results. Among all the skin types, HCWs with oily skin (64, 62.1%) were prone to face resurgence of acne or new-onset acne. The most common sites of eruption of acne were along the cheeks (45.1%) followed by the nose (40.9%). Majority of the population suffered from mild acne. Moderate and severe acne eruption was particularly observed in those wearing N-95 and surgical masks.Conclusion: The use of face masks is associated with high rates of acne eruption. Disseminating the guidelines and indications of World Health Organization (WHO) regarding proper use of mask, encouraging awareness among HCWs and following proper doffing and donning protocol as endorsed by Centers for Disease Control and Prevention (CDC) will possibly minimize the adverse reactions.Keywords: acne, facemask, healthcare worker, COVID-19